2016
DOI: 10.1021/acscatal.6b00099
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Geometry and Oxidation State Requirements of Corner-Sharing MnO6 Octahedra for Water Oxidation Catalysis: An Investigation of Manganite (γ-MnOOH)

Abstract: Surface-directed corner-sharing MnO 6 octahedra within numerous manganese oxide compounds containing Mn 3+ or Mn 4+ oxidation states show strikingly different catalytic activities for water oxidation, paradoxically poorest for Mn 4+ oxides, regardless of oxidation assay (photochemical and electrochemical). This is demonstrated herein by comparing crystalline oxides consisting of Mn 3+ (manganite, γ-MnOOH; bixbyite, Mn 2 O 3 ), Mn 4+ (pyrolusite, β-MnO 2 ) and multiple monophasic mixed-valence manganese oxides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
151
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(168 citation statements)
references
References 74 publications
15
151
1
1
Order By: Relevance
“…The catalytic cycle was facilitated by the defect sites in layers of edge‐sharing MnO 6 including corner‐sharing MnO 6 species . Also, the high OER efficiency of γ‐MnOOH (compared to various manganese oxides) shows that tetragonally distorted Mn(III)O 6 octahedra with corner‐sharing is regarded as more crucial structural motif for catalysis …”
Section: Lattice Constants and Unit Cell Volume Calculated From Xrd Psupporting
confidence: 89%
See 1 more Smart Citation
“…The catalytic cycle was facilitated by the defect sites in layers of edge‐sharing MnO 6 including corner‐sharing MnO 6 species . Also, the high OER efficiency of γ‐MnOOH (compared to various manganese oxides) shows that tetragonally distorted Mn(III)O 6 octahedra with corner‐sharing is regarded as more crucial structural motif for catalysis …”
Section: Lattice Constants and Unit Cell Volume Calculated From Xrd Psupporting
confidence: 89%
“…To enhance the efficiency of synthetic Mn‐based electrocatalysts, structural parameters for activity enhancement and rate‐determining process have been copiously investigated . The superior OER activity for mixed‐valent MnO x to MnO nanocrystal indicated that the edge‐sharing MnO 6 octahedra with high valency served as a key structural motif for catalysis .…”
Section: Lattice Constants and Unit Cell Volume Calculated From Xrd Pmentioning
confidence: 91%
“…[17] At potentials above 1.2 Vv ersus RHE, MnO 2 starts to dissolve. [34,35] On the basis of the currentu nderstanding, Mn 3 + is critical for enhancing the OER [36][37][38][39] and ORR [29] activities. with similar heats of formation that crystallize in different crystal structures.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al. () found that the electrocatalytic activity of Mn(IV) oxide for water oxidation was very poor, while Mn(III) oxide (MnOOH or Mn 2 O 3 ) showed significantly more active for water oxidation (Gorlin & Jaramillo, ). These results suggest that it is Mn(III) that perhaps plays a key role in the removal of ammonium by MnO x .…”
Section: Introductionmentioning
confidence: 99%